Peran Public Relations Dalam Membangun Citra Perusahaan Melalui Program Corporate Social Responsibility PT. Antam Tbk. Kolaka Sulawesi Tenggara - Zulfiah Larisu; Sumadi Dilla; La Ode Herman (Jayapangus Press, 2020)
Company do not at moment's notice Corporate Social Responsibility (CSR) in running its effort. Some company applying CSR is exactly assumed to behave too social. There is also a success company apply CSR, but society exactly look into company fail to draw public sympathy. Target of company give benefit at society at the same time create image, but inacceptable sometimes better. This matter happened because CSR done conducted is not arranged and not supported by good concept. Target of this article is to make efficient and effective CSR concept for the application of by company.